2016
DOI: 10.15537/smj.2016.12.15739
|View full text |Cite
|
Sign up to set email alerts
|

A stepwise introduction of a successful antimicrobial stewardship program

Abstract: ObjectivesTo analyze and evaluate the safety and cost-effectiveness of a gradually-implemented antimicrobial stewardship programs (ASP) in a tertiary care center.MethodsProspective data were collected from an ASP that was gradually introduced between April 2012 and December 2013 in 6 hospital departments, over successive periods of 3 months each. A multidisciplinary team supervised antibiotic use and regulated pharmacy dispensations of a list of restricted antimicrobials (RAs). Indicators were prospectively mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 42 publications
1
34
0
3
Order By: Relevance
“…At a hospital level, evidence suggests the implementation of ASPs in some Saudi tertiary hospitals [7][8][9] and these ASPs are mainly led by infectious diseases (ID) consultants, with limited input from microbiologists and hospital pharmacists [7,8]. However, due to the shortage of ID consultants and microbiologists [2], these antimicrobial stewardship initiatives face sustainability challenges in tertiary care and are less likely to be implemented in secondary care where adoption of ASPs remains low [10].…”
Section: Introductionmentioning
confidence: 99%
“…At a hospital level, evidence suggests the implementation of ASPs in some Saudi tertiary hospitals [7][8][9] and these ASPs are mainly led by infectious diseases (ID) consultants, with limited input from microbiologists and hospital pharmacists [7,8]. However, due to the shortage of ID consultants and microbiologists [2], these antimicrobial stewardship initiatives face sustainability challenges in tertiary care and are less likely to be implemented in secondary care where adoption of ASPs remains low [10].…”
Section: Introductionmentioning
confidence: 99%
“…Beberapa artikel penelitian dalam kajian sistematis ini menunjukkan adanya penurunan temuan beberapa patogen resisten setelah diimplementasikannya ASP, antara lain seperti methicillin-resistant Staphyloccus aureus (MRSA), 33,35,47,48 carbapenem-resistant Acinetobacter baumanii 34,35 , extended spectrum beta-lactamase (ESBL)-producing Eschericia coli, 35 ESBL-producing Klebsiella pneumoniae, 35 dan multi-drug resistant (MDR)-Acinetobacter baumanii. 51 Namun demikian, dalam kajian sistematis ini juga ditemukan bahwa beberapa jenis patogen resisten justru mengalami peningkatan pada periode setelah implementasi ASP. 33,34 Hal ini dapat dipahami dengan mempertimbangkan bahwa beberapa mekanisme resistensi dapat berkembang dan disebarkan antarjenis patogen yang berbeda melalui plasmid.…”
Section: Upper-middle-income Economies (N) High-income Economies (N)unclassified
“…Dampak positif terakhir dari implementasi ASP ialah adanya penurunan biaya pengadaan (analisis dilakukan menggunakan perspektif rumah sakit) atau biaya penggunaan antibiotik (analisis dilakukan menggunakan perspektif pasien). 35,38,42,44,45,[47][48][49][50][51][52] Penurunan biaya tersebut dapat disebabkan oleh keberhasilan tim ASP dalam memberikan rekomendasi kepada dokter mengenai penghentian penggunaan antibiotik pada kasus yang tidak terbukti infeksi bakteri, 43,45 memperpendek waktu penggunaan antibiotik, 40,42,49 dan menurunkan jumlah penggunaan antibiotik kombinasi. 28,29 Meski demikian, perlu disampaikan bahwa rekomendasi perubahan atau penghentian terapi antibiotik tidak selalu diterima oleh dokter; 43 besar persentase penerimaan dokter terhadap rekomendasi yang diberikan berkisar antara 52% sampai 74,5%.…”
Section: Upper-middle-income Economies (N) High-income Economies (N)unclassified
See 1 more Smart Citation
“…computerisation of records, decision support system) [5]. Numerous studies [6][7][8] have shown the effectiveness of ASP and its interventions; and recently, there is an _________________________________________ increasing emphasis in evaluating cost-effectiveness upon implementation of these interventions. The recent reviews involved a large variation in the method and depth of ASP being economically evaluated (i.e.…”
Section: Introductionmentioning
confidence: 99%